A proposed model for paradigmatic relations within an emergent discipline - Glazier, Jack D. (Anales de Documentación, 2002)
This article is the vehicle for purposing a model for mapping the processual change associated with disciplinary and paradigmatic development. Change of this sort is contingent on the degree of consistency achieved within theory groups. Consistency, in this case, is equated theory and paradigm dominance. The symbolic interactionist tradition supplies the assumptions on which the model is grounded Examination of the model is accomplished by contrasting it with Thomas Kuhn's theory. The recent history of library and information science education in the U.S. serves as context and exemplar for application of the model